A Universal Law of Economic Variation - Clark, John Bates (Quarterly Journal of Economics, 1894)
Journal Article A Universal Law of Economic Variation Get access John Bates Clark John Bates Clark Amherst College, Massachusetts Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 8, Issue 3, April 1894, Pages 261–279, https://doi.org/10.2307/1883455 Published: 01 April 1894